Proceedings of the 8th International Conference on Kansei Engineering and Emotion Research : KEER 2020, 7-9 September 2020, Tokyo, Japan /: KEER 2020, 7-9 September 2020, Tokyo, Japan. (2020) - Unknown
No abstract available